A centre for provision of assistive technology services in Singapore. Issue 1 (May 2014) - Hoh Tan, Chuan; Yee Chia, Woon; Yong, Sarah
Abstract : Traditionally, persons with acquired disabilities in Singapore receive rehabilitation services at Rehabilitation Centres or Community Hospitals. They would be prescribed activities of daily living aids and mobility aids to improve their independence in their day-to-day activities. Assistive Technology (AT) devices were not considered as a part of rehabilitation as therapists lacked the knowledge and resources in prescribing appropriate technological solutions to their clients. The services of the Specialised Assistive Technology Centre (ATC) at the Society for the Physically Disabled (SPD) have changed this perspective and greatly improved service provision and awareness. This article highlights the role of occupational therapists in the provision of AT to complement rehabilitation therapy services for persons with disabilities and in improving rehabilitation outcomes related to AT usage for this population.